Coronavirus Disease 2019–Related Stigma in China: A Descriptive Study - Zhao, Li; Wang, Zhen; Guan, Jian; Shen, Panyan; Zhao, Wen; Zuo, Guoguo (Frontiers in Psychology, 2021)
Coronavirus disease 2019 (COVID-19) tremendously impacts the physical and mental health of humans worldwide. Consequently, studies on COVID-19 remain extensive. However, most of them were mainly focused on the pathological mechanisms and treatment methods from medical perspectives. Various reports have indicated that COVID-19 is closely related to stigma and discrimination, but little statistical information has been integrated quantitatively to describe the situation in China. Thus, this study investigated the COVID-19-related stigma of individuals. We collected the online survey data from 1,920 Chinese participants from October to December 2020. Findings showed that 306 (15.94%), 285 (14.84%), 265 (13.80%), and 100 (5.21%) participants endorsed stigma toward individuals in high-risk areas, recovered patients with COVID-19, families of recovered patients with COVID-19, and frontline healthcare providers, respectively. To understand the possible factors that could impact the COVID-19-related stigma, knowledge about COVID-19 was investigated. Generally, knowledge about COVID-19 was negatively associated with COVID-19-related stigma in general, while no significant relationship existed between the knowledge about COVID-19 and the COVID-19-related stigma in the groups who had held COVID-19-related stigma. Ultimately, individuals showed COVID-19-related stigma toward recovered patients and their families, individuals in high-risk areas, and frontline healthcare providers to some extent. The results of this study can provide reference to nations, governments, and organizations in addressing the stigma issues raised by the COVID-19 pandemic.